Impacts of EMI filter on high speed interconnects for digital circuits design - Chang, Richard Weng Yew (2013)
Today's digital data lines are clocking at very high speed, in excess of 100MHz with rise time in the sub-nano second range. The effects of EMI radiation even from short traces are becoming significant and cannot be ignored. The use of resistive termination versus the EMI filter has long been a compromise in terms of cost and necessity. EMI compliance is now becoming a major design challenge for product development rather than a mere good-to-have specification of low emission. This paper carries out a comprehensive study on filter selection, application, impact on receiver waveform signal integrity and far-field emission suppression using a full-wave electromagnetic simulator (CST Microwave Studio). This study will provide high-speed digital designers an in-depth assessment of the use of EMI filter for radiation suppression in high-speed digital layout.